Biopsychosocial Factors and Perceived Disability in Saleswomen with Concurrent Low Back Pain - Praneet Pensri; Prawit Janwantanakul; Puangsoi Worakul; Thanes Sinsongsook (Elsevier, 2010)
Objectives: To quantify disability level in salespeople with concurrent low back pain (LBP) and to determine the relative associations between demographic, occupational, psychosocial and clinical factors and back disability. LBP is the most common cause of work-related disability in people under 45 years of age and the most expensive cause of work-related disability, in terms of workers' compensation and medical expenses. Evidence suggests high prevalence of LBP in salespeople. Methods: A cross-sectional survey was conducted in which 184 saleswomen with a current episode of self-reported LBP working in a large up-scale department store filled out a battery of 6 self-administered questionnaires and received a standardised physical examination. Results: Saleswomen with concurrent LBP had low disability levels. Factors significantly associated with disability were pain intensity, measured by a visual analogue scale, in the past week (p < 0.001), physical and mental health status (p < 0.001, p = 0.003, respectively), fear avoidance scores for both work and physical activities (p = 0.031, p = 0.014, respectively), past history of LBP (p = 0.019), and self-reported frequency of pushing or pulling objects placed in high positions during work (p = 0.047). A significant level (45%) of the variance in disability status was explained by these variables. Conclusion: In clinical management of LBP workers who required prolonged standing, such as salespeople, clinicians should look for modifiable risk factors associated with disability. Specific measures need to be taken to prevent disability due to LBP among salespeople.